2010
DOI: 10.1097/meg.0b013e32832e9d41
|View full text |Cite
|
Sign up to set email alerts
|

The response to hepatitis B vaccine: does it differ in celiac disease?

Abstract: The response to HBV vaccine in celiac children who were compliant to GFD is not different from a healthy population. CD may be one of the immune diseases associated with a high rate of HBV vaccine nonresponse but it might not be permanent and treatment with GFD and compliance to the treatment may ameliorate the immune response to HBV vaccine in celiac children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 33 publications
5
49
1
1
Order By: Relevance
“…Conversely, 3 of 10 (30%) patients with CD who completed vaccination at or after one year of age failed to develop anti-HBs. Ertem et al (11) reported that the response to HBV vaccine in celiac children who were compliant with a gluten-free diet was not different from that of healthy controls. They suggested that compliance with the glutenfree diet may ameliorate the immune response to HBV vaccine in children with CD.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, 3 of 10 (30%) patients with CD who completed vaccination at or after one year of age failed to develop anti-HBs. Ertem et al (11) reported that the response to HBV vaccine in celiac children who were compliant with a gluten-free diet was not different from that of healthy controls. They suggested that compliance with the glutenfree diet may ameliorate the immune response to HBV vaccine in children with CD.…”
Section: Discussionmentioning
confidence: 99%
“…94 However, the response to HBV vaccine in coeliac children who were compliant with a gluten-free diet is no different from that of the healthy population. 95 Thus, coeliac disease may be one of the immune diseases associated with a reduced response to HBV vaccine; however, this lack of response might not be permanent, and a gluten-free diet and compliance with treatment may ameliorate the immune response to the vaccine. 95 In this respect, Melmed et al 92 evaluated immunogenicity with the 23-valent pneumococcal polysaccharide vaccine in IBD patients receiving both anti-TNF agents and immunomodulators, IBD patients not receiving any immunosuppressive therapy, and in healthy controls.…”
Section: What Factors Affect the Efficacy Of Hbv Vaccination In Ibd Pmentioning
confidence: 99%
“…95 Thus, coeliac disease may be one of the immune diseases associated with a reduced response to HBV vaccine; however, this lack of response might not be permanent, and a gluten-free diet and compliance with treatment may ameliorate the immune response to the vaccine. 95 In this respect, Melmed et al 92 evaluated immunogenicity with the 23-valent pneumococcal polysaccharide vaccine in IBD patients receiving both anti-TNF agents and immunomodulators, IBD patients not receiving any immunosuppressive therapy, and in healthy controls. Inflammatory bowel disease patients who received combination immunosuppressive therapy mounted a less effective immune response than patients with IBD who received non-immunosuppressive therapy and controls, both of which exhibited a similar good response.…”
Section: What Factors Affect the Efficacy Of Hbv Vaccination In Ibd Pmentioning
confidence: 99%
“…Gluten might be implicated because both hepatitis B surface antigen (HBsAg) protein fragments and gliadin peptides bind to HLA-DQ2 molecules and induce proliferation of T lymphocytes. Competition between the proteins may result in defective antibody production (6)(7)(8).…”
mentioning
confidence: 99%